The Place of Women in the Administrative and Diplomatic System of Central Africa (La Place de la Femme Dans le Dispositif Administratif et Diplomatique d’Afrique Centrale) - BEKONO, Cyrille Aymard (The Gender Truth Journal, 2025)
This study analyzes the place that community institutions in the Central African sub-region grant to women. The objective is to urge political decision-makers in this sub-region to strengthen the involvement of women in the community, administrative, and diplomatic systems. The exploitation of a variety of primary and secondary sources, in light of constructivist theory, in a systemic approach that assumes that all parts of the work are interrelated, was necessary to understand the evolution of women’s integration in sub-regional institutions. The findings of this study show that women have long experienced marginalization within community institutions, due to their late schooling and many other prejudices. This explains the limited number of women capable of working in the administration of the community institution. However, the promotion of women’s political rights under the aegis of the UN, since the 1990s, has contributed substantially to the integration of women in all sub-regional activities. This justifies the fact that, during the creation of CEMAC, women were considered within the institution. Résumé Cette étude analyse la place que les institutions communautaires de la sous-région d’Afrique centrale accordent à la femme. L’objectif est d’exhorter les décideurs politiques de cette sous-région à renforcer l’implication de la femme dans le dispositif administratif et diplomatique communautaire. L’exploitation d’une variété de sources primaires et secondaires, à la lumière de la théorie constructiviste, dans une démarche systémique qui suppose que toutes les parties du travail soient en interrelation, a été nécessaire pour comprendre l’évolution de l’insertion de la femme dans les institutions sous-régionales. Ainsi, il ressort de cette étude que la gent féminine a longtemps connu une marginalisation au sein des institutions communautaires, à cause de sa scolarisation tardive et de nombreux autres préjugés. Cela explique le nombre limité des femmes capables de travailler dans les administrations de l’institution communautaire. Cependant, la promotion des droits politiques de la femme sous l’égide de l’ONU, depuis la décennie 1990, contribue substantiellement à l’intégration de la femme dans toutes les activités sous-régionales. Ce qui justifie le fait que, lors de la création de la CEMAC, la femme connaît une considération dans l’institution.